Manajemen Kepala Sekolah Sebagai Penggerak Mutu Pendidikan di Madrasah Aliyah Darul Ulum Kubu Raya - M. Jali (Jurnal Ilmiah Edukatif, 2023)
Driving schools and school principals are the foundation of hope for education, and teachers are the driving force to achieve the goals of quality education. The school principal's leadership is a determining factor in driving organizational change and management in schools; its existence is not only a symbol but also a determinant of the success and quality of education in schools. This research aims to determine the management of school principals as a driver of educational quality at MA Darul Ulum Kuala Dua. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out using interviews, observation, and documentation. Primary data sources are principals, and secondary data sources are teachers, students, books, and relevant research journals. The results of this research show that the Principal of MA Darul Ulum School can improve the quality of education based on the following points: human resource management, student management, building and yard management, and the principal's supervisory duties.